Menyibak Penerapan PSAP 07 Aset Bersejarah terhadap Penyajian Laporan Keuangan: (Studi pada Museum Daerah Kabupaten Sambas) - Mukaromah, Lailatul; Noviriani, Eliza; Zurmansyah, EE; Munandar (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This research aims to understand and study how the accounting treatment in the financial reporting of assets against historical assets in the Regional Museum of Sambas Regency in accordance with PSAP Number 07 of 2010. Researchers chose the Sambas Regency regional museum also experienced obstacles in the process of recording, valuation and presentation in the financial statements. The research method uses qualitative where the researcher observes the object to get natural or not made up data. The results obtained that the process of recording, valuing and presenting historical assets at the Sambas Regency Regional museum is in accordance with PSAP 07 of 2010. However, there are still some historical assets in the museum that have not been accommodated and have not been reported at the Regional Finance Agency of Sambas Regency.